Rev-erb-α modulates skeletal muscle oxidative capacity by regulating mitochondrial biogenesis and autophagy - Woldt, Estelle (2013)
The nuclear receptor Rev-erb-α modulates hepatic lipid and glucose metabolism, adipogenesis and the inflammatory response in macrophages. We show here that Rev-erb-α is highly expressed in oxidative skeletal muscle and plays a role in mitochondrial biogenesis and oxidative function, in gain- and loss-of function studies. Rev-erb-α-deficiency in skeletal muscle leads to reduced mitochondrial content and oxidative function, resulting in compromised exercise capacity. This phenotype was recapitulated in isolated fibers and in muscle cells upon Rev-erbα knock-down, while Rev-erb-α over-expression increased the number of mitochondria with improved respiratory capacity. Rev-erb-α-deficiency resulted in deactivation of the Stk11–Ampk–Sirt1–Ppargc1-α signaling pathway, whereas autophagy was up-regulated, resulting in both impaired mitochondrial biogenesis and increased clearance. Muscle over-expression or pharmacological activation of Rev-erb-α increased respiration and exercise capacity. This study identifies Rev-erb-α as a pharmacological target which improves muscle oxidative function by modulating gene networks controlling mitochondrial number and function.